Konsolidacja zniszczonej mechanicznie dekoracji emalierskiej na miedzi i jej stopach za pomocą żywic termoplastycznych - Tomaszewska, Arletta; Tomaszewska-Szewczyk, Alina (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
The objects of study were metal artefacts decorated with enamel. It wasestablished that the main reason of destruction was mechanical damage thatcaused cracking and loosening of the enamel, and – in extreme cases – shapedeformation and losses in the decoration layer. The main problem to be solvedwas the choice of methods and means for the consolidation of the exfoliatedenamel as well as for setting it on the metal. Moreover, a method had to beestablished for dealing with shape deformation. A typology of damages wasdeveloped, so that criteria might be established by which to choose means ofconsolidation for mechanically destroyed enamel. On the basis of the research,a methodology of further proceedings was proposed, involving preparationsfulfilling the main postulates.The object of study was a group of 60 objects made of copper and its alloysand decorated with enamel. These were Chinese and Japanese artefacts from theRegional Museum in Toruń and the National Museum in Poznań, dated fromthe 17th century to the early 20th century. The decorative techniques includedcloisonné, champlevé and painted enamel.The following typology of mechanical damages was developed, based onthe state of the enamelled objects:1. with the metal ground exposed:– exfoliation;2. with the metal ground unexposed:– delamination: blistering, with partial exfoliation,– cracking: longitudinal, radial, circular, reticular.The main causes of damage were use, shape deformation, technologicalfaults and corrosion of the metal surface.The following criteria were taken into account for selecting a means ofconsolidation for mechanically damaged enamel:– transparency and colourlessness,– good adhesiveness to metal surfaces and enamel,– elasticity (especially if an enamel layer is to be strengthened whileremoving shape deformation),– water-resistance,– lack of corrosive influence,– easy applicability: viscosity, easy excess removal, room temperatureapplicability.The preparations selected for further study by the above criteria includedacrylic resins popular in conservation (Paraloid A-10S, A-101, A-21, B-44,B-48N, B-67, B-72, B-99N, F-10, NAD-10V) and other thermoplastic resinsused for paint layer consolidation on metal surfaces (Beva 371, Plexisol P550).Preliminary assessments of such factors as the preparations’ viscosity,elasticity, relative hardness, and water-resistance, made it possible to select threethermoplastic resins for further tests: Paraloid B-44 and Paraloid F-10.Further experiments were conducted on sheet copper samples decoratedwith enamel. The samples were mechanically damaged, and the cracks,delaminations and exfoliations of the enamel layer were treated with thepreparations in question. Luminophores were admixed to the preparations tomonitor their penetration and distribution in the layer under UV light. Furthertests examined the preparations’ adhesiveness to the ground and the enamelunder prolonged exposure to water; the anti-corrosive protection they offered tothe metal; and their influence on shape deformation removal processes.On the basis of the research, preparations were selected for the treatmentof mechanically damaged enamel, their choice dependent on the type of damage.A methodology was proposed for excess preparation removal. Safe methodsof object preparation for shape distortion removal were established, as well asmethods of proceeding in cases where the original shape cannot be restored.Several badly damaged items then underwent conservation.